Characterization of Aerosol Particles Produced by a Skyscraper Demolition by Blasting. (October 2017) - Wagner, Andrea C.; Bergen, Anton; Brilke, Sophia; Bühner, Bertram; Ebert, Martin; Haunold, Werner; Heinritzi, Martin; Herzog, Stephan; Jacobi, Stefan; Kürten, Andreas; Piel, Felix; Ramme, Alfons; et al.
Abstract: We present a study characterizing aerosol particles resulting from a skyscraper blasting. High PM 10 mass concentrations with a maximum of 844.9 μg m -3 were present for a short time period of approximately 15 minutes. They result in a day mean of 32.6 μg m -3 compared to a 27.6 μg m -3 background not exceeding the 50 μg m -3 EU maximum permissive value. The increase in particle number concentration was less pronounced with a maximum concentration of 6.9 ⋅ 10 4 cm -3 compared to the local background value of 1.8 ⋅ 10 4  cm -3 . The size-resolved number concentration shows a single mode of ultrafine particles at approximately 93 nm. The spatial distribution of deposited dust was investigated with Bergerhoff glass collection vessels, showing a decrease with distance. In the deposited dust samples the concentrations of twelve metals was determined, non of them exceeded the regional background concentrations significantly. The chemical composition of individual particles emitted by the demolition was studied by Scanning Electron Microscopy. They were mainly concrete and steel particles, with 60% calcium carbonates, 19% calcium sulfates, 19% silicates and 2% steel. In energy-dispersive X-Ray Spectroscopy, no fibers like asbestos were observed. Using a broad spectrum of instruments and methods, we obtain comprehensive characterization of the particles emitted by the demolition. Abstract : Graphical abstract: Abstract : Highlights: Aerosol particles resulting from a skyscraper blasting are characterized. The blasting produced high mass concentration for a short time. Particles were rather small with a mode diameter around 100 nm. The blasting did not lead to an enhanced concentration of fibers.